Golden Unicorn - Whitney, Phyllis A (Doubleday, 1976)
When her adoptive parents die, Courtney Marsh begins her search for her real parents and, guided only by a golden unicorn necklace, finds her way to a reclusive East Hampton family whose peculiar, entangling affairs are not what she has expected
Keywords: Suspense Thrillers; Literature & Fiction